simplifique as expressoes. a) (x+5)2-x(x+3) b) (x-4)2 -(x-1)2 c) (x+1)2-(x-2)2
d) (-x+3)2 -2x (4-x)
me ajude e para hoje
Soluções para a tarefa
Respondido por
1
a) (x+5)2-x(x+3) = x^2 + 10x + 25 - x^2 - 6x - 9 ==> 4x + 16
b) (x-4)2 -(x-1)2 = x^2 - 8x + 16 - x^2 + 2x - 1 ==> -6x + 15
c) (x+1)2-(x-2)2 = x^2 + 2x + 1 - x^2 + 4x - 4 ==> 6x - 3
d) (-x+3)2 -2x (4-x) = x^2 - 6x + 9 + 2x^2 - 8x ==> x^2 - 4x + 9
Perguntas interessantes
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Administração,
1 ano atrás